Validation of football locomotion categories derived from inertial measurements - Lentz-Nielsen, N.; Madeleine, P. (Sports Engineering, 2023)
In sports like football, knowledge concerning physical demands is used for training sessions and matches. Inertial measurement units are often used to estimate physical demands. Catapult Sports has recently developed, based on acceleration and gyroscope data, the Football Movement Profile algorithm that enables to categorize physical demands into locomotion categories facilitating the interpretation of practitioners. The aim of this study was to assess the validity of the locomotion predictions derived from the Football Movement Profile during controlled drills. Data were collected from 41 elite youth football players executing controlled drills replicating linear locomotion at five velocities, i.e., 5.4, 12, 18, 19.8, and 21.6 km/h and non-linear locomotion. An overall good agreement (> 95%) was found for lower velocity linear movements (= 12 km/h), but the agreement decreased with increasing velocities (67% at 21.6 km/h). A poor agreement was found for the lower velocity non-linear movements (78%) but increased with higher velocities (> 98%). The relationship between the magnitude and type of classification errors among the players suggests that it would be beneficial to establish individual calibration thresholds for the algorithm.